IMPLEMENTASI PROGRAM PELAYANAN KEPEMUDAAN PADA DINAS PEMUDA DAN OLAHRAGA PROPINSI SULAWESI UTARA - TOMBUKU, MONICA RAHEL (JURNAL ADMINISTRASI PUBLIK, 2014)
ABSTRAK: Acording to the intruction law no.40 years 2009, sector regulations north celebes province no.3 years 2008 and government north celebes regulations no.48 years 2008, then youth and sportdepartement north celebes province to determine various prioritation program in younger service sector but in the implementation stril find various problems and constrain. This research direction will know how implementation program younger services youth and sport departement of north celebes province.This research is using qualitative method. The program of implementation younger service focused to four elements/program is the same manner as to proposed in implementation model from Edward III is comunication, capacity source disposition, and bereaucracy stucture. Data source (informant) that has interview 13 people consist or 8 people official / employee youth and sport departement north celebes province and 5 peoples leadership / manejer from miles and huberman.The research showed; 1. Program youger service has not communicated / commitment with good; 2. Capacity source for implementation availeble with incomplete especially human of capacity source / employee; 3. disposition (socialization and consistent employee / execute high enough ; and 4. Bureucracy structure (mechanics and procedur is simple enough, and task deviding and cleary responsibility)Based on the output research attractived conclusions that all programs youngerservice the detemined youth and sport departement north celebes province can implementated not maximal, especially in comunication sector.Based on conclusions research output suggested : (1) All of the importantaspect in policy implementation draft / younger services program efective method (communication, capacity source, disposition and structure), still need increased; (2) communication between programmer and program receiver must be fixed and estimation alocation for younger services programneed increased so that younger service programs can reach out all youth organization exist in north celebes province.Berdasarkan hasil penelitian tersebut ditarik kesimpulan bahwa semua program pelayanan kepemudaan yang ditetapkan Dinas Pemuda dan Olahraga Propinsi Sulawesi Utara dapat diimplementasi dengan cukup baik dan berhasil.keywords : policy implementation/programs, younger services.